METHODOLOGY FOR DEVELOPING PEDAGOGICAL MASTERY OF FUTURE TEACHERS BASED ON INTERACTIVE PLATFORMS IN THE DIGITAL EDUCATION SPACE (American Journal of Interdisciplinary Research and Development, 2026)
The rapid transformation of education under the influence of digital technologies has fundamentally reshaped the professional profile of future teachers, making pedagogical mastery not only a matter of subject knowledge and methodological competence but also an outcome of effective engagement with interactive digital platforms within a comprehensive digital learning environment. This article proposes and substantiates a methodological framework for developing the pedagogical mastery of pre-service teachers through interactive platforms in the context of a digital educational space, emphasizing the integration of pedagogical interaction, reflective practice, and competency-based digital instruction. The study is grounded in contemporary theories of digital pedagogy, constructivist learning, and professional competence development, and it employs a mixed-methods research design combining qualitative pedagogical analysis with quantitative evaluation of learning outcomes. The results demonstrate that systematic use of interactive platforms—such as learning management systems, collaborative digital tools, and simulation-based environments—significantly enhances pedagogical communication skills, instructional design competence, and reflective teaching abilities among future teachers. The findings confirm that pedagogical mastery in the digital education space is most effectively developed through an integrative methodological approach that aligns technological affordances with pedagogical objectives, learner-centered interaction, and continuous professional reflection. The article contributes to the theoretical and practical advancement of teacher education by offering a scalable, methodologically grounded model for pedagogical mastery development in digitally enriched learning environments.